'Do I feel lucky?': Moral Luck, Bluffing and the Ethics of Eastwood's Outlaw-Lawman in Coogan's Bluff and the Dirty Harry Films. Issue 1 (February 2017) - Deshaye, Joel
Abstract : In Coogan's Bluff (1968) and the Dirty Harry films, Clint Eastwood's characters often invoke luck when they want unpredictable others to assume some responsibility to stop violence, thereby implicating moral luck in heroism. In the famous 'Do I feel lucky' scene from Dirty Harry (1971), Eastwood's character might not be bluffing, but he is giving luck a role in justice. In this case and others, his character's unconventional responsibility should prompt reconsideration of his character's virtue. Viewers must also decide where the deceptive or rule-breaking policeman locates the responsibility for his actions.